Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1007/bf02913078
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the age dependent changes in serum adenosine deaminase activity and its changes in hepatitis

Abstract: Serum Adenosine deaminase (ADA) activity in normal healthy control subjects increases upto 30 years, remains steady between 31-60 years of age and shows a steep increase in the age group of 61-70 years. This was compared with serum aspartate transaminase (AST) and alanine transaminase (ALT) activity which also showed a gradual increase upto 40 years of age and decreased thereafter. The activities of serum ADA, AST and ALT increased in patients with hepatitis of all age groups compared to their respective contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…It has been demonstrated that the presence of these isoenzymes in serum, regardless of their amount, has a diagnostic value. Previous studies found the elevated activity of ADA2 in a variety of conditions such as acquired immunodeWciency syndrome (AIDS), T-cell lymphoblastic malignancies, tuberculosis, liver diseases, rheumatoid arthritis, and myasthenia gravis (MG) [6,[8][9][10][11][12][13][14]. We have recently reported the similar data for primary immunodeWciency disorders (PIDs) [7].…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…It has been demonstrated that the presence of these isoenzymes in serum, regardless of their amount, has a diagnostic value. Previous studies found the elevated activity of ADA2 in a variety of conditions such as acquired immunodeWciency syndrome (AIDS), T-cell lymphoblastic malignancies, tuberculosis, liver diseases, rheumatoid arthritis, and myasthenia gravis (MG) [6,[8][9][10][11][12][13][14]. We have recently reported the similar data for primary immunodeWciency disorders (PIDs) [7].…”
Section: Introductionsupporting
confidence: 53%
“…They are traditionally divided into organ-speciWc and non-organ-speciWc disorders [12]. Systemic lupus erythematosus (SLE) appears to be a prototypic example of the latter, whose manifestations associate with the production of a plethora of autoantibodies, mostly against nucleus DNA.…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation is the lack of age-matched validation cohort. Age-dependent serum adenosine deaminase activity may have had an impact on this result [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, since the average ALT level for six of seven patients was Ͻ40 U/liter but Ͼ20 U/liter, these results illustrate the occurrence of host immune selection even with a slight increase in average ALT level. Although the cutoff of 20 U/liter may seem arbitrary, the ALT levels of hepatitis-free populations of different age groups have never exceeded this level (13,41). To this extent, an ALT level of 20 U/liter may represent the action of host immunity against HBV.…”
Section: Discussionmentioning
confidence: 99%